Aplikasi Penerimaan dan Pengeluaran Kas pada CV. Satu Holiday Tour dan Travel Bandung - Suprihatin, Eti; Astryani, Arinta Fadhila (STIE Atma Bhakti, 2025)
CV. Satu Holiday Tour and Travel Bandung is a service company operating in the tourism travel agency sector and was founded in 2016. All cash receipt and disbursement transactions are recorded using a cash receipt and disbursement book by the Finance Department based on proof of cash receipts and disbursements used. The aim of this research is to create an application that can be used to overcome problems regarding cash receipt and disbursement transactions at CV. One Holiday Tour and Travel regarding cash receipts and disbursements. The methodology used in this application is the prototype method with design tools Flowmap, Data Flow Diagram (DFD) and Entity Relationship Diagram (ERD). Meanwhile, the implementation of this application design uses Visual Basic for Application with a Microsoft Access database. The results of this cash receipt and disbursement application can facilitate the process of recording and recapitulating cash receipt and disbursement transactions, so that the presentation of cash receipt reports and cash disbursement reports becomes more accurate and faster. This application has been tested and confirmed by CV. One Bandung Tour and Travel holiday, and the results were in accordance with the company's needs.